FYN regulates cell adhesion at the blood-testis barrier and the apical ectoplasmic specialization via its effect on Arp3 in the mouse testis - Yang, Yue; Yao, Mingxia; Zeng, Jie; Zheng, Dongwang; Li, Qin; Ni, Ya; Xiao, Xiang (Frontiers in Immunology, 2022)
FYN is a non-receptor tyrosine kinase of the SRC family that facilitates virus entry across epithelial tight junctions. However, the role of FYN in mammalian testes in maintaining the blood-testis barrier (BTB) integrity and the adhesion of germ cells to Sertoli cells are not well defined. Here, we show that FYN is a component of the BTB and the apical ectoplasmic specialization (ES) at Sertoli-Sertoli and Sertoli-spermatid interfaces, respectively, and is expressed extensively in mouse testes during postnatal development. FYN was shown to be structurally linked to the actin and microtubule-based cytoskeletons. An in vivo model was used to explore the modulatory effect of FYN on BTB and apical ES dynamics within the testes when adult mice were treated intraperitoneally with CdCl2 (3 mg/kg body weight). The CdCl2-induced epithelial restructuring was associated with a transient increase in the interaction between FYN and the actin branching/nucleation protein Arp3, as well as an induction of Arp3 phosphorylation, which possibly lead to actin cytoskeleton remodeling, resulting in BTB damage and germ cell loss in the seminiferous epithelium. Based on the results, we propose a model in which FYN and Arp3 form a protein complex that is responsible for junction reorganization events at the apical ES and the BTB. It is also possible for viruses to break through the BTB and enter the immunoprivileged testicular microenvironment via this mechanism.